Bisphosphonate use and risk of renal cell carcinoma: A population‐based case‐control study. Issue 5 (4th January 2019) - Chung, Benjamin I.; Hellfritzsch, Maja; Ulrichsen, Sinna P.; Sørensen, Henrik T.; Ehrenstein, Vera
Abstract: The purpose of this study was to evaluate the association between the use of bisphosphonates and the risk of developing renal cell carcinoma (RCC). We conducted a case‐control study in Denmark, using data linked from population‐based health and administrative registries. We identified all cases of RCC from 1996 to 2013 and sampled population controls in a 10:1 ratio from the underlying population free of RCC, while matching on sex, birth year and calendar time. Bisphosphonate use before RCC diagnosis, excluding the year leading up to the diagnosis, was measured using outpatient prescription dispensations. We used conditional logistic regression to compute crude and adjusted odds ratios (ORs) comparing ever vs. never bisphosphonate use in doses indicated for treatment of osteoporosis, overall and stratified by sex, with the OR estimating the incidence rate ratio. We also examined the effects by cumulative dose and specific agent. There were 2748 RCC cases and 27 480 controls. The adjusted ORs for ever vs never bisphosphonate use were 1.07 (95% confidence interval: 0.94‐1.22) overall; 1.15 (1.00‐1.32) for women; and 0.78 (0.54‐1.12) for men. Smoking could not be directly controlled for in the analysis. We found a weak association between use of oral bisphosphonates and risk of renal cell carcinoma in females. The observed association could be due to confounding by cigarette smoking, and future studies are required to assess this association further.